Longitudinal Relationship Between Time-Out and Child Emotional and Behavioral Functioning. Issue 1 (January 2020) - Knight, Rachel M.; Albright, Jeremy; Deling, Lindsay; Dore-Stites, Dawn; Drayton, Amy K.
ABSTRACT: Objective: Time-out is a widely used child discipline strategy and one of the only strategies currently recommended by the American Academy of Pediatrics. Despite its widespread use and significant evidence to support its effectiveness in decreasing problem behavior, time-out is often suggested to be harmful or ineffective by the popular media and select professional organizations. Empirical evidence regarding possible side effects of time-out is limited. The present study examined the relationship between reported use of time-out and child emotional and behavioral functioning and parent-child relationships using longitudinal, archival data. Methods: The study used archival, longitudinal data from the Early Head Start Research and Evaluation study. This study tracked families with children in Early Head Start at 3 different time points as follows: baseline (aged 0–3 years), pre-kindergarten, and fifth grade. Parent interviews, including questions on the use of time-out, were conducted when the children were 36 months old. Indicators of child emotional and behavioral health were measured at 36 months, pre-K, and fifth grade. Statistical analyses were completed to assess for potential side effects of time-out on child behavioral and emotional functioning and parent-child relationships. Results: Analyses for all outcome variables suggest no significant difference for children whose parents reported using time-out versus those who did not. Conclusion: Parental reported use of time-out was not associated with long-term negative outcomes. Further research in this area is necessary to continue to address the multitude of concerns related to time-out that are presented by the media. Abstract : This article has supplementary material on the web site: www.jdbp.org.